MECHANISMS OF HEPATITIS B VIRUS PERSISTENCE AND IMMUNE EVASION IN THE LIVER - Mamedov Arzu Nazirovich (Web of Journals Publishing, 2024)
This article delves into the etiology, mechanisms of development, prevalence, types, clinical implications, and consequences of chronic Hepatitis B Virus (HBV) infection. HBV is a significant global health challenge due to its unique ability to persist and evade the immune system, often resulting in lifelong infection and severe liver disease.
Keywords: Hepatitis B Virus, liver, immune evasion, chronic infection, hepatocytes, immune tolerance, viral persistence, immune modulation, hepatocellular carcinoma, cccDNA, immunotherapy.